DISTRIBUTED CREATIVITYAND ECOLOGICAL DYNAMICS: A CASE STUDY OF LIZA LIM'S 'TONGUE OF THE INVISIBLE' - Clarke, E; Doffman, M; Lim, L (2013)
This essay addresses distributed creative processes in the preparation and performance of a new musical work-Tongue of the Invisible by Liza Lim, commissioned by the Cologne-based Ensemble musikFabrik. Situating the research within a broadly ecological perspective, and in the specific context of the interface between composition, improvisation, and performance, the study offers a social and distributed understanding of creative production. From the sizeable body of audio and video data recorded during the preparatory workshops, rehearsals, and performances of the new work, as well as interviews and discussions with the players, conductor, and composer, three discrete episodes from the piece are analysed in some detail. These three examples demonstrate the complex interweaving of musical role, institutional structure, spontaneity and intervention, and designed underdetermination in the creation of a performance, and are couched within an explanatory framework anchored in principles of ownership, signification, and the interanimation of social materials, understood as the components of a dynamic musical ecosystem. © 2013 The Author.